Impact of the COVID-19 Pandemic on Corneal Transplantation: A Report From the Italian Association of Eye Banks - Mencucci, Rita; Cennamo, Michela; Ponzin, Diego; Genzano Besso, Federico; Pocobelli, Giulio; Buzzi, Matilde; Nucci, Carlo; Aiello, Francesco (Frontiers in Medicine, 2022)
Purpose To analyze the impact of COVID-19 on Italian corneal transplantation from March-2020 to February 2021 compared to the same timeframe of the 2 previous years, in order to identify potential consequences of a global pandemic on corneal procurement and transplantation services during this time. Methods This national, multicentric, retrospective cohort study evaluated data collected from 12 (100%) Italian eye banks from March 2020 to February 2021 (Group A). The number of tissues collected, distributed and discarded were compared with the same time-frame of the 2 previous years: 2019 and 2018 (group B and C, respectively). The different type of transplants performed were reported. Data were analyzed using a non-parametric Friedman test. Results Corneal procurement and the percentage of distributed tissues reduced in 2020 by more than 30% and 15%, respectively, compared to the 2 previous years. During the pandemic corneal transplant surgery showed only a modest drop: the number of the penetrating keratoplasties (PKs) and the anterior lamellar keratoplasties (ALKs) decreased by about 30% and 20% in comparison with groups B and C, respectively; between the Endothelial Keratoplasties (EKs), the Descemet membrane endothelial keratoplasty (DMEK) increased slightly from March 2020 to February 2021 Conclusions Italy was one of the first countries most affected by the outbreak of COVID-19, and the Italian government adopted severe measures to limit viral transmission. The pandemic generated several implications in corneal transplant activity during the first lockdown. Then an efficacious reaction with constant, vigorous work led to a resumption of transplant surgery to a near-normal standard. The increase of EKs, despite the pandemic, is a sign that the advance in corneal transplantation has gone ahead and it continues to evolve.